2022
DOI: 10.3389/fpsyt.2022.933570
|View full text |Cite
|
Sign up to set email alerts
|

The role of metformin in treatment of weight gain associated with atypical antipsychotic treatment in children and adolescents: A systematic review and meta-analysis of randomized controlled trials

Abstract: IntroductionSecond-generation antipsychotics are associated with significant weight gain. The aim of this systematic review and meta-analysis was to determine the efficacy and safety of metformin for the treatment of weight gain in children and young adults treated with second-generation antipsychotics.MethodsWe followed PRISMA guidelines to evaluated studies published before March 2020 in Medline, Google Scholar, PubMed, Cochrane library database, annual scientific sessions of the American Psychiatric Associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…A previous meta‐analysis assessed the efficacy and safety of metformin in reducing weight secondary to antipsychotic use in children 52 . While this study reported a 2 kg weight reduction when taking metformin, along with a statistically significant reduction in BMI z‐score, it is notable that, like topiramate, metformin did not significantly impact metabolic outcomes such as triglyceride, total cholesterol, LDL, HDL, and blood sugar levels.…”
Section: Discussionmentioning
confidence: 77%
“…A previous meta‐analysis assessed the efficacy and safety of metformin in reducing weight secondary to antipsychotic use in children 52 . While this study reported a 2 kg weight reduction when taking metformin, along with a statistically significant reduction in BMI z‐score, it is notable that, like topiramate, metformin did not significantly impact metabolic outcomes such as triglyceride, total cholesterol, LDL, HDL, and blood sugar levels.…”
Section: Discussionmentioning
confidence: 77%
“…There are other known pharmacological strategies that have been tried as add-on to adipogenic antipsychotics and are still used in clinical practice, e.g., Metformin, which is an anti-diabetic drug that has proven e cacy in wight loss among patients who take antipsychotics and suffer weight gain (41,42). The use of metformin as adjunctive therapy to treat weight gain was implemented when non-pharmacological treatment failed.…”
Section: Discussionmentioning
confidence: 99%